Sorry to say, but pilots’ decisions were not irrational - Perezgonzalez JD (British Psychological Society Digest Research)
Fradera’s Digest (2016) makes for interesting reading both for aviators and cognitive psychologists alike. Fradera reports on a research article by Walmsley and Gilbey (2016) and the Digest seems pretty accurate to the contents commented upon (in a way, thus, whatever praises or criticisms are raised apply equally to the latter article). The Digest is interesting because what it says is quite relevant in principle but rather misleading in practice. That is, the actual results reported by Walmsley and Gilbey, do not seem to support the portrayal of pilots as biased and irrational, a portrayal which originates in the interpretation of those results based on a flawed statistical technique—null hypothesis significance testing, or NHST. In a nutshell, Fradera opted to summarize the interpretation of (some) outputs made by Walmsley and Gilbey instead of re-interpreting those outputs anew within the context of the methodology and the results described in the original article, as I shall argue.
Keywords: NHST; VFR flying; cognitive biases; correction of the research literature; Better Science